Glory be - Arceneaux, Danielle (Arceneaux, Danielle. Glory Broussard mystery., 2023)
"It's a hot and sticky Sunday in Lafayette, Louisiana, and Glory has settled into her usual after-church routine, meeting gamblers at the local coffee shop, where she works as a small-time bookie. Sitting at her corner table, Glory hears that her best friend--a nun beloved by the community--has been found dead in her apartment. When police declare the mysterious death a suicide, Glory is convinced that there must be more to the story. With her reluctant daughter--who has troubles of her own--in tow, Glory launches a shadow investigation into Lafayette's oil tycoons, church gossips, a rumored voodoo priestess, nosey neighbors, and longtime ne'er-do wells. As a Black woman of a certain age who grew up in a segregated Louisiana, Glory is used to being minimized and overlooked. But she's determined to make her presence known as the case leads her deep into a web of intrigue she never realized Lafayette could harbor."--Amazon